Inhibition of the host antiviral response by Nipah virus: current understanding and future perspectives. (May 2016) - Satterfield, Benjamin A; Geisbert, Thomas W; Mire, Chad E
Nipah virus (NiV) is a lethal paramyxovirus that has recently emerged as a human pathogen capable of causing acute respiratory disease and encephalitis. Like many viral pathogens, NiV has developed multiple means of antagonizing the host antiviral response. The viral proteins responsible for this antiviral inhibition are encoded in the NiV P gene and include the P, V, W and C proteins, which contain various unique and overlapping roles. This review examines the current data on inhibition of the host antiviral response for each of these proteins gathered from viral protein expression systems, in vitro data using recombinant NiV mutants and from in vivo studies using recombinant NiV mutants, as well as a future perspective regarding the direction of the field.